Risk factors associated with urogenital schistosomiasis: a multilevel assessment approach using an Oversampling Schistosomiasis Survey (SOS) community-based, Plateaux region, Togo 2022 - Penelope Vounatsou; Fiona M Fleming; Rachel Pullan; Katherine Gass; Smaila Alidou; Hélène E Kamassa; Fiali Lack; Essoham Ataba; Efoe Sossou; Manani Hemou; Kossi Yakpa; Mawèké Tchalim; et al. (BMJ Public Health)
Background Urogenital schistosomiasis is endemic in Togo. Since 2010, Togo has used preventive chemotherapy to control the disease and periodically assess its impact. This study aimed to estimate the prevalence of urogenital schistosomiasis and identify associated risk factors among school-age children in three districts of the Plateaux Region of Togo.Methods A cross-sectional study surveyed school-age children in three Togo districts, using an oversampling strategy of door-to-door visits to collect urine samples, metadata and lifestyle data. Statistical analyses, including descriptive and multilevel regression, were used to determine prevalence and investigate individual/community risk factors associated with urogenital schistosomiasis and infection intensity.Results This study surveyed 6400 children, uncovering a 15.0% prevalence of urogenital schistosomiasis (95% CI: 14.1% to 15.8%). Notably, 48.3% (95% CI: 45.1% to 51.5%) showed heavy-intensity infections, averaging 38 eggs per 10 mL (range: 0–9688). Key risk factors included age (adjusted OR (aOR)=1.9), swimming in surface water (aOR=2.6) and residing in the Ogou district (aOR=11.2), while the Est-Mono district posed a lower risk (aOR=0.2). Factors such as gender, with boys at higher risk (aOR=1.7), age (aOR=2.9), school attendance (aOR=2.4) and swimming in surface water (aOR=4.7) were linked to infection intensity. Consumption of public tap water (aOR=2.4; 95% CI: 1.0 to 5.2) and residing in Ogou (aOR=28.6) increased intensity, whereas living in Est-Mono (aOR=0.0; 95% CI: 0.0 to 0.08) or using rainwater (aOR=0.0; 95% CI: 0.0 to 0.4) decreased it.Conclusions The prevalence and intensity of urogenital schistosomiasis were found to be correlated with household and behavioural risk factors. Integrating these factors into national control programmes and improving access to safe water and sanitation facilities will be crucial in eliminating this disease as a public health concern in Togo.